Multi-domainsdispatching method for power system considering energy storage. Issue 1 (February 2021) - Ge, Weichun; Liu, Debao; Liu, Tao; Wang, Shunjiang; Liu, Junfa; Hu, Lei
Abstract: Reasonably arranging the matching of power sources is an effective mean to improve the capacity of new energy consumption. Using the dispatching characteristics of the transferable load of the energy storage systems can play an important role in the actual dispatch of the power system. From the perspective of flexible scheduling, a multi-domain scheduling method is proposed, which comprehensively considers the influence of factors such as load, wind power output random fluctuations and system adjustment capabilities, and redistributes it into three control domains. That is, the normal control domains with the goal of completely absorbing wind power, anomaly control domain where the energy storage systems needs to be used to absorb wind power, and the emergency control domain where there is no regulation ability and forced to abandon wind. To maximizing clean energy consumption, CPLEX software is used to optimize output and realize multi-domain green economic dispatch. The calculation example shows that this method can effectively improve the absorption capacity of clean energy.